B-cell multicentric lymphoma in a creole mare - a case report - T.G. Cristo; L. Marian; T.C. Valente; J.J.S. Sá; E.V. Rocha; N.C.C.A. Fernandes; C.S.C. Borges; R.A. Casagrande (Arquivo Brasileiro de Medicina Veterinária e Zootecnia)
ABSTRACT Lymphomas are neoplasms of origin in lymphocytes, rarely reported in equines, and classified as multicentric, alimentary, mediastinal, cutaneous, and extranodal in this species. This paper aims to report the case of a Creole mare with multicentric lymphoma. The case of a mare with weight loss, lethargy, and lymphadenomegaly unresponsive to therapy is reported. Clinical examination showed tachycardia, tachypnoea, and dyspnoea, in addition to enlargement and stiffening of palpable lymph nodes, suggestive of hyperplasia by aspiration cytology. The animal showed progressive worsening, not responding to therapy, and death occurred during the second clinical evaluation. Necropsy showed an increase in the size of all palpable lymph nodes and internal lymph nodes. Marked thoracic and abdominal effusions were also observed. Microscopically, the neoplastic proliferation of large lymphocytes was noted, infiltrated in multiple organs. Immunohistochemical (IHC) evaluation of tumor showed positivity for PAX-5 and Ki-67. The association of histopathology and IHC results allowed classifying the neoplastic process as a multicentric large B-cell lymphoma. This type of lymphoma in equines tends to have a silent clinical behavior, with a progressive evolution and clinical condition usually culminating in death.